If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18(c + -1) + -18 = p Reorder the terms: -18(-1 + c) + -18 = p (-1 * -18 + c * -18) + -18 = p (18 + -18c) + -18 = p Reorder the terms: 18 + -18 + -18c = p Combine like terms: 18 + -18 = 0 0 + -18c = p -18c = p Solving -18c = p Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-18'. c = -0.05555555556p Simplifying c = -0.05555555556p
| t^2(t^4-10t^2+9)=0 | | 2(3y-12)+4=-4 | | 5=-32+b | | Y=100-60 | | t/4-17=13 | | 7x+6=30-x | | 6y+3=3y+3 | | -7-4x=-6x-27 | | 4x+5-4x=6 | | 2x=-4-2y | | 15-6x/12=3/4 | | P(2)=4.05 | | M=33 | | 9y-3yx=a | | x^2+9-2=0 | | -8-7(y+2)=p | | 2g+5=-5g+5 | | y=5+-1x | | 13x/-11 | | 4x-6=4y | | 6y+11+3y+15=360 | | 7/8y=32 | | 5b+11=56-46b | | -2x^2-16x-29= | | 7(2m-3)=2m-15 | | 81b=156a | | 17=5x-7x+3 | | X^2+x+320=0 | | 12x+32=6x+62 | | 3a=3(a+1) | | 2-3m=5-m | | X+2y=336 |